Genetic effects of released swimming crab (Portunus trituberculatus) on wild populations inferred from mitochondrial control region sequences. (18th August 2018) - Shan, Binbin; Hui, Min; Zhang, Xiumei; Liu, Shude; Cai, Shanshan; Song, Na; Tu, Zhong; Wang, Yunzhong; Wang, Sijie; Gao, Tianxiang
Abstract: Along the coast of Shandong Province in China, an extensive hatchery-release programme has been conducted for more than 10 years. However, no information has been reported concerning the long-term effects on the wild population resulting from the release of large numbers of juveniles in Portunus trituberculatus . In this study, sequence variation of swimming crab P. trituberculatus based on the mitochondrial control region was investigated for 946 swimming crabs at the releasing sites from 2012 to 2014. The result showed that the wild P. trituberculatus was characterized by high genetic diversity indices, and not significantly different from the previous study. Low F ST values were estimated among the groups of different years and different sites, which suggested no genetic differentiation found in the wild population after the stock enhancement programme. Hence, the long-term extensive hatchery release programme has not affected the genetic structure of wild P. trituberculatus populations along the coast of Shandong Province.